How Will the Patient Protection and Affordable Care Act Affect Liability Insurance Costs? - David I. Auerbach , Paul Heaton, and Ian Brantley (RAND Corporation, 2014)
The Patient Protection and Affordable Care Act (ACA) (Pub. L. 111-148, 2010) promises to bring substantial changes to the U.S. health care system, including potentially expanding coverage to millions of uninsured Americans. Although considerable research is already under way examining how the ACA will affect medical providers, consumers, and private health insurers, much less is known about how the ACA will affect liability insurers, despite the fact that liability insurers reimburse tens of billions of dollars for medical care each year in the United States. This report identifies several channels through which the ACA might affect liability insurance payments—also referred to here as insurer costs—summarizes the conceptual basis for and existing evidence for these channels and, where possible, calculates rough estimates of the sizes and directions of expected impacts. Although lingering uncertainties surrounding how the ACA implementation will proceed make offering precise quantitative predictions of the law’s impact unrealistic at this point, the report does aim to identify lines and states where the ACA’s effects may be more profoundly felt, areas in which impacts are expected to be modest, and highlight domains in which substantial uncertainty still exists. It represents one of the first systematic empirical explorations of the ACA’s potential effects on liability insurers and, as such, should be informative to insurance industry professionals, policymakers, and regulators. This research was supported by Swiss Re and also in part by pooled contributions to the RAND Institute for Civil Justice. The Swiss Re Group is a leading wholesale provider of reinsurance, insurance, and other insurance-based forms of risk transfer. Dealing directly and working through brokers, Swiss Re’s global client base consists of insurance companies, medium-sized to large corporations, and public-sector clients. Swiss Re’s public research program supports research on cutting-edge topics at the intersection of risk management, insurance and public policy